Population variability in heat shock proteins among three Antarctic penguin species - Barbosa, Andrés; Merino, Santiago; Benzal, Jesús; Martínez, Javier; García-Fraile, Sonia (Polar Biology, 2007)
Heat shock proteins (HSPs) are synthesised under stressful conditions such as exposure to elevated temperatures, contamination, free radicals, UV light or pathophysiological states resulting from parasites and/or pathogens. HSPs function to protect cells by means of modulation of protein folding. In Antarctica, these proteins have been studied in such organisms as protozoa and fishes, without attention to geographical variation. We studied the variation of HSP70 and HSP60 levels in Gentoo, Adelie and Chinstrap penguins among different populations along the Antarctic Peninsula from King George Island (62°15′S) to Avian Island (67°46′S). Our results show that the northern population of Gentoo penguin showed higher levels of HSP70 and HSP60 than the southern population. High temperature, human impact and immunity as a proxy for parasites and diseases in northern locations could explain such variation. Adelie penguin only showed significant geographical variation in HSP70, increasing north to south, a pattern perhaps related to increased UV radiation and decreased temperatures from north to south. Chinstrap penguin shows no population differences in the variation in neither HSP70 nor HSP60, although HSP70 showed marginally significant differences. Sexual differences in the level of these proteins are also discussed. This study has been funded by the Acción Especial project REN2001-5004/ANT of the Spanish Ministry of Education and Science. The projects CGL2004-01348/ANT (PINGUCLIM) and POL2006-05175 (BIRDHEALTH-SPAIN) supported AB while the paper was written. Peer reviewed